أحــــــــــكام إشتراكات الضمـــــــــان الإجتماعــــــــي في التشريع الجزائري - زهيـــــر, حــــاقـــــة (My University, 2021)
يهدف هذا البحث إلى دراسة وتبيان أحكام إشتراكات الضمان الإجتماعي وكيفية تحصيلها ونرى أن كل هذا يتجسد في العلاقة القائمة بين المستخدم وهيئة الضمان الإجتماعي، وذلك من خلال التطرق إلى مفهوم الضمان الإجتماعي ونشأته وطبيعته القانونية المتجسدة في الإلزام والأولوية والإجبارية، وتلي الطبيعة توضيح الموارد التمويلية من دفع إشتراكات مستحقة لتغطية المخاطر المضمونة في مجال الضمان الإجتماعي، ويدرس الموضوع أيضا التأمين عن الأخطار التي يتعرض إليها المؤمن من أمراض مهنية، وحوادث عمل وعجز....الخ، من خلال توضيح مقدار التأمين التي تغطيه هيئة الضمان الإجتماعي للمستخدم وذوي الحقوق. إلى أن نخلص أخيرا الى الآليات و الطرق الجبرية لتحصيل الإشتراكات وفقا لأحكام الضمان الإجتماعي، التي توضح لنا أن نظام الضمان الإجتماعي يعتمد في تحصيل الإشتراكات على إقتطاعات المستخدم كمصدر لتمويل له ويلعب دورا مهما في الحفاظ على التوازن المالي لهذه الهيئة. This research aims to study and clarify the provisions of social security Contributions and how to collect them، and we see that all of this is embodied in the relationship between the user and the social security Authority، by addressing the concept of social security its origin and legal nature embodied in the obligation، priority and compulsion and the nature follows the clarification of the financing resources from payment due contribution to cover guaranteed risks to which the insrured is exposed from occupational diseases، work accidents disability …etc، by clarifying the amount of insurance covered by the social security authority for the user and the rights holders.Until we finally come to the compulsory mechanisms and methods for collecting contributions in accordance with the provisions of social security، which shows us that the social security، system depends in collecting. Contributions on user deductions as a source of financing for him and plays an important role in maintaining the financial balance of this body
ماستر قانون اداري
Keywords: الضمان الإجتماعي، الإشتراك، الخطر الإجتماعي، طرق التحصيل.; Social security، contribution، social risk، collection methods.